2020
DOI: 10.31234/osf.io/bjxm8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intersections of official and family language policy in Quebec

Abstract: The current paper describes a study that sought to determine the beliefs, practices, and needs of parents living in Montreal, Quebec, who were raising their children bi/multilingually. The parents (N = 27) participated in a total of nine focus group and individual interviews in which they discussed their family language policies (language ideologies, practices, and actions taken to maintain a language). Through rounds of deductive and inductive coding and analysis, family language policies regarding English an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Although these factors were not measured directly in our study, families’ language policies might have impacted their home literacy practices. Parents of bilingual French–English children in Montréal have positive views about bilingualism and value both languages, given their importance in Québec society (Ballinger et al, 2020). Consequently, these families likely have language policies intended to support their children’s bilingualism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although these factors were not measured directly in our study, families’ language policies might have impacted their home literacy practices. Parents of bilingual French–English children in Montréal have positive views about bilingualism and value both languages, given their importance in Québec society (Ballinger et al, 2020). Consequently, these families likely have language policies intended to support their children’s bilingualism.…”
Section: Discussionmentioning
confidence: 99%
“…Many bilingual families have positive views of bilingualism and aim to support language and literacy development in both of the families’ languages, not just the majority language (Genesee, 2004; King & Fogle, 2006). Positive views of bilingualism have been reported by parents of Cantonese–English children in the United States (Leung & Uchikoshi, 2012), Turkish–Dutch children in the Netherlands (Backus et al, 2010; Bezcioglu-Goktolga & Yagmur, 2018), bilingual families in Australia (Piller & Gerber, 2018), and of particular interest to this paper, French–English families in Montréal (Ballinger et al, 2020). More specifically, parents of French–English bilingual children reported that they valued bilingualism both for their children to be able to communicate with family and friends, and for the potential advantages it might offer for education and future employment opportunities (Ballinger et al, 2020).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…In the first phase of our research project about Quebec-based parents raising children multilingually, we conducted exploratory interviews and focus groups with 27 Montreal-based parents who were raising infants/toddlers aged 0-3 years with multiple languages in the home (Ballinger et al, 2020). The resulting qualitative data indicate that children's cognitive development was an important issue on parents' minds.…”
Section: The Dimensionality Of Attitudesmentioning
confidence: 99%